Feasibility of surgical procedures of invasive thymoma invading the neighbouring organs - Kumar, Ajay; Ning, Jiang Ge (International Surgery Journal, 2019)
Thymomas are the commonest anterior mediastinal compartment neoplasm, which constitutes about 20 and 50% respectively of all mediastinal and anterior compartment tumors occurring in the adult population. The various staging systems of thymomas have been defined on the basis of the degree of invasiveness. According to the WHO classification, there are six histological types of thymic epithelial tumors. The most important prognostic factor is the stage according to Masaoka’s system. The treatment of thymomas involves combinations of surgery, radiation, and chemotherapy. The determination of which combination is chosen is reflected mostly by the stage of the disease. In the case of invasive disease, radiation therapy is often used as adjuvant treatment. Although invasive thymoma commonly infiltrates neighbouring mediastinal structures, its extension into the superior vena cava (SVC) and consequent SVC occlusion are rare. In this kind of cases, the urgent removal of the thymoma and radical resection of the tumour infiltrating the SVC represents the reasonable option.